2007
DOI: 10.1038/sj.pcan.4500950
|View full text |Cite
|
Sign up to set email alerts
|

Photoselective vaporization of the prostate. Review of cost implementation to BPH treatment

Abstract: Effective treatment of benign prostatic hyperplasia (BPH) involves not only a reduction of symptom scores and the prevention of serious complications, but also an improvement in overall patient's quality of life and cost effectiveness. There is a paucity of data regarding cost effectiveness when the pharmacologic, the minimally invasive and the surgical treatments of BPH are compared. The potassium-titanyl-phosphate laser prostatectomy seems to be a safe and effective treatment option both in the short and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
(79 reference statements)
0
2
0
2
Order By: Relevance
“…The complications of BPH, including urinary retention, urinary infection, reduced renal function, and indwelling urinary catheter, eventually lead to reduced social activities in particular [ 2 ]. These problems brought a rapid increase in social expenses from 4 billion to 26 billion dollars annually, a trend that is continuously increasing at the moment [ 3 ]. This fact implies that medical costs could be saved to a great extent if BPH were properly managed in our society.…”
Section: Introductionmentioning
confidence: 99%
“…The complications of BPH, including urinary retention, urinary infection, reduced renal function, and indwelling urinary catheter, eventually lead to reduced social activities in particular [ 2 ]. These problems brought a rapid increase in social expenses from 4 billion to 26 billion dollars annually, a trend that is continuously increasing at the moment [ 3 ]. This fact implies that medical costs could be saved to a great extent if BPH were properly managed in our society.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping all of this in mind, Alivizatos et al concluded that although preliminary results of cost-analysis studies of PVP are in favor of PVP versus TURP, further evidence is certainly needed to support this. 59 …”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, también se pueden encontrar objeciones a esta técnica. Una de ellas es el elevado coste económico, aunque no existen en la literatura estudios concluyentes al respecto, y los disponibles hasta ahora determinan que la FVP es menos cara que la RTUp 5,6 . Otro de los puntos débiles no cuestionables de la FVP es la ausencia de estudios prospectivos aleatorizados randomizados con seguimiento a largo plazo, que avalen los resultados hasta ahora publicados (a diferencia de su gran "competidor" que es la enucleación prostática con láser Holmium).…”
unclassified